Penerapan Model Pembelajaran Inkuiri Terbimbing Untuk Meningkatkan Keterampilan Proses Sains (KPS) Siswa Sekolah Dasar - Rahmani Rahmani; Abdul Halim; Zulkarnain Jalil (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
The aim of the study was to determine the improvement of student science process skills in the material properties of the light after applying the guided inquiry learning model. The hypothesis of the study was the application of the guided inquiry learning model can improve the student science process skills in the material properties of the light. The quasi-experimental was used in this study and one group pre and post tests design was performed. Â The population of this study was all fifth-grade students of primary school (SD) Negeri 37 Banda Aceh in 2014/2015 school year, amounting to 30 students. All of the population members were used as the samples. The test and questionnaire were used to collect the data. Â The students were given the pretest and posttest learning using the same instrument at the beginning and end of the study. The data were subjected to the Â statistical t-test. Based on the results of normality and homogeneity test data, it was obtained that data are normal and homogeneous. The results showed that science process skills were obtained that t = 29.1274, while the value table = 1.6827. Therefore tcount t-table then Ho was rejected and Ha was accepted. Hence, it is concluded that the application of guided inquiry learning model can improve the science process skills of students in the material properties of the light